Additive In Vitro Antiplasmodial Effect of N-Alkyl and N-Benzyl-1, 10-Phenanthroline Derivatives and Cysteine Protease Inhibitor E64. (7th June 2010) - Wijayanti, Mahardika Agus; Sholikhah, Eti Nurwening; Hadanu, Ruslin; Jumina, Jumina; Supargiyono, Supargiyono; Mustofa, Mustofa
Abstract : Potential new targets for antimalarial chemotherapy include parasite proteases, which are required for several cellular functions during the Plasmodium falciparum life cycle. Four new derivatives of N -alkyl and N -benzyl-1, 10-phenanthroline have been synthesized. Those are (1)- N -methyl-1, 10-phenanthrolinium sulfate, (1)- N -ethyl-1, 10-phenanthrolinium sulfate, (1)- N -benzyl-1, 10-phenanthrolinium chloride, and (1)- N -benzyl-1, 10-phenanthrolinium iodide. Those compounds had potential antiplasmodial activity with IC50 values from 260.42 to 465.38 nM. Cysteine proteinase inhibitor E64 was used to investigate the mechanism of action of N -alkyl and N -benzyl-1, 10-phenanthroline derivatives. A modified fixed-ratio isobologram method was used to study the in vitro interactions between the new compounds with either E64 or chloroquine. The interaction between N -alkyl and N -benzyl-1, 10-phenanthroline derivatives and E64 was additive as well as their interactions with chloroquine were also additive. Antimalarial mechanism of chloroquine is mainly on the inhibition of hemozoin formation. As the interaction of chloroquine and E64 was additive, the results indicated that these new compounds had a mechanism of action by inhibiting Plasmodium proteases.